PENGARUH STRATEGI BISNIS, KEPEMILIKAN KELUARGA DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Sartika, (2022)
This study aims to determine the significant positive effect of business strategy, family ownership and political connections on tax avoidance in companies listed on the Indonesia Stock Exchange in the 2019-2020 period. This research is a type of quantitative research that uses secondary data in the form of financial statements and company annual reports. This study used a sample of 150 companies listed on the Indonesia Stock Exchange. The technique for analysing the data in this research is using panel data regression model selection test, classical assumption test, hypothesis testing and multiple linear regression test. Based on the results of data analysis, it can be concluded that (1) business strategy has no effect on tax avoidance, (2) family ownership has no effect on tax avoidance, (3) political connections have no effect on tax avoidance, (4) company size does not have an influence on tax avoidance. effect on tax avoidance, (5) leverage has a significant positive effect on tax avoidance.